Improving Short Story Text Writing Skills Through the Application of Process Approach in Grade IX A Students of SMP Negeri 1 Dusun Utara - Mimil, Mimil; Nurhidayah, Nurhidayah; Efendi, Anwar (Journal of Science and Education (JSE), 2026)
This study aims to enhance students’ short story writing skills through the implementation of a process approach among Grade IX A students at SMP Negeri 1 Dusun Utara. The research employed a Classroom Action Research (CAR) design, conducted in two cycles. Each cycle comprised four stages: planning, implementation of actions, observation, and reflection. The participants of the study were 30 students from Grade IX A. Data were collected through pre-action tests, observations, and evaluations of students’ written works after the intervention. The findings revealed a significant improvement in students’ short story writing skills following the application of the process approach. The Minimum Mastery Criterion (KKM) was set at 70. In the first cycle, the average score for students’ writing skills was 70, while in the second cycle, the average score increased to 83. This improvement encompassed four main aspects assessed: theme, orientation, complication, and resolution. Therefore, it can be concluded that the implementation of the process approach is effective in improving the short story writing skills of Grade IX A students at SMP Negeri 1 Dusun Utara.